Role of Molecular Biology as Diagnostic tools of Infectious disease- an update - Begum, Afroza; Begum, Shahanara (Bangladesh Journal of Medical Microbiology, 2013)
No Abstract DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16935 Bangladesh J Med Microbiol 2011; 05 (02): 27-29